Agro não é tudo: a expansão da monocultura da soja sobre os territórios quilombolas na Amazônia Oriental - DIAS, Gustavo Francesco de Morais (Universidade Federal do Pará, 2023)
The Amazon biome has undergone intense transformations in the last two decades, primarily due to the advancement of agriculture. In this regard, the current Federal Constitution recognizes quilombola communities as cultural groups with the right to the demarcation of their lands. However, in the Amazon, this right has been threatened by the expansion of agribusiness. Therefore, the research question of this thesis is how the dynamics of land use and land cover affect the territories belonging to traditional populations and conservation units. Additionally, the influences of the Brazilian Forest Code (CFB), Soy Moratorium, and Rural Environmental Registry (CAR) on the expansion of soybean cultivation in the region were investigated. This study focused on the municipalities of Belterra, Mojuí dos Campos, and Santarém-PA, in the state of Pará, Brazil. In addition to the municipalities, the Tapajós National Forest (FNT) and the quilombos (traditional Afro-Brazilian communities) present in the municipality of Santarém were also analyzed, including Murumurutuba, Bom Jardim, Maria Valentina, Arapemã, Tiningu, and Murumuru. Mapbiomas data from the period 2000 to 2019 were used for the analysis of the region's images. The Institutional Analysis and Development (IAD) Framework and Qualitative Comparative Analysis (QCA) methodologies were employed to describe the interaction among the actors involved in the expansion of soybean production in the Santarém Plateau region. Fuzzy Logic was used to describe the data derived from questionnaires, interviews, and secondary sources. The analyses conducted revealed significant deforestation in the municipalities of Mojuí dos Campos and Belterra due to the expansion of soybean production and pasture, which has increased exponentially in recent years. In addition, inconsistencies were observed between the Forest Code and the soy moratorium, allowing producers to advance with soybean production in the Amazon. Furthermore, it was observed that the expansion of soybean cultivation is driven by a series of public and private investments in infrastructure, particularly in road and highway construction, port development, and subsidies to large-scale farmers. In the Santarém Plateau region, it was observed that quilombola communities face difficulties related to access to public health services, infrastructure, and lack of state support. The study identified an expansion of soybean cultivation within and near quilombola communities starting in 2014, which raises concerns among these peoples regarding the preservation of their territories, way of life, and the increasing damage to local natural resources. It was also identified that forest and soybean variables are necessary conditions to explain changes in land use and land cover concerning traditional populations. Therefore, only when analyzed together are they sufficient to explain the phenomenon, meaning that improvements in forest and soybean conditions are necessary to prevent damages resulting from changes in land use and land cover on the quilombola populations in the Santarém region.